The impact of self-concept on destination preference. - Heng, Amanda Li Hui. (2010)
This study takes a multidimensional perspective in enhancing the understanding of how Destination-Self-Congruity (DSC) determines Singaporean tourists’ preferences to visit Japan and Australia. The application of self-concept has received little attention from tourism researchers, especially in the Asian context. For a more holistic explanation of factors affecting Singaporeans’ destination preferences, we considered not only DSC, but also the utilitarian attributes of a destination and the demographics of tourists to that destination.